Tools of transport telematics : 15th International Conference on Transport Systems Telematics, TST 2015, Wrocław, Poland, April 15-17, 2015. Selected papers /: 15th International Conference on Transport Systems Telematics, TST 2015, Wrocław, Poland, April 15-17, 2015. Selected papers. (2015) - Unknown
No abstract available